Analysis Of Human Resource Planning On Employee Recruitment Policy AT The Special Coal Terminal Of Pt. Cakra Transindo Utama - Syahrial Fadli; Marzuki Alie (Publikasi Indonesia, 2023)
human resource planning (HRM) activities can be said to be the beginning of all human resource management (MSDM) activities. However, HR planning is not the only burden borne by the Company's HR managers. All managers in an organization or company plan the needs and availability of human resources by the interests and progress of the organization. HR Planning is the process of how a company or organization meets current and future workforce needs. A literature review is a set of explanations for a very important part of a research report. The literature in this chapter reveals the thoughts or theories that underlie and support research. The theory presented in the literature review chapter is useful for researchers to explain the relationship between several concepts that will be used to explain research problems so that research results will be obtained that can answer the problem formulation contained in the research title. This study applies a qualitative design, namely research that focuses on on general principles that form the basis of the manifestation of a symptom of human life, or also patterns analyzed from socio-cultural indications through the culture of the community to obtain representations regarding the ongoing examples. According to John W. Creswell in the book Research Design, qualitative research is: So, in general, the notion of human resource planning is the process of analysis and identification by the organization of the need for human resources so that the organization can determine the steps that must be taken to achieve its goals. In addition, the importance of holding human resource planning is that the organization will have a clear picture of the future, and be able to anticipate the shortage of the required quality workforce.